2013
DOI: 10.1248/bpb.b12-00819
|View full text |Cite
|
Sign up to set email alerts
|

Pre-therapeutic Assessment of Plasma Dihydrouracil/Uracil Ratio for Predicting the Pharmacokinetic Parameters of 5-Fluorouracil and Tumor Growth in a Rat Model of Colorectal Cancer

Abstract: We investigated the correlation between plasma ratio of dihydrouracil/uracil (UH2/Ura), a possible surrogate biomarker of hepatic dihydropyrimidine dehydrogenase (DPD) activity, and 5-fluorouracil (5-FU) treatment efficacy in rats with colorectal cancer (CRC). 5-FU pharmacokinetic and pharmacodynamic studies were performed using DPD circadian variation in rats with 1,2-dimethylhydrazine-induced CRC. By plotting tumor volume after 5-FU treatment against pre-therapeutic plasma UH2/Ura, we inferred a linear relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…Our previous study confirmed that this circadian rhythm existed, and that the ratio of UH2/Ura in plasma was correlated with DPD levels in the liver of CRC rats [16]. Furthermore, by plotting the CL tot and AUC 0-∞ after single or repeated 5-FU administration to CRC ratsagainsttheratioofUH2/Urainplasma,measured before the PK experiments, a linear relationship was inferred [16]. Boisdron-Celle et al reported that measuring the UH2/Ura ratio appeared to be the single best method for determining DPD deficiency and activity level for clinical use [30].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Our previous study confirmed that this circadian rhythm existed, and that the ratio of UH2/Ura in plasma was correlated with DPD levels in the liver of CRC rats [16]. Furthermore, by plotting the CL tot and AUC 0-∞ after single or repeated 5-FU administration to CRC ratsagainsttheratioofUH2/Urainplasma,measured before the PK experiments, a linear relationship was inferred [16]. Boisdron-Celle et al reported that measuring the UH2/Ura ratio appeared to be the single best method for determining DPD deficiency and activity level for clinical use [30].…”
Section: Discussionsupporting
confidence: 80%
“…reported that the levels of DPD in rat liver were highest at around noon and lowest at around midnight , indicating that rat DPD levels peaked during rest time and declined at active times. Our previous study confirmed that this circadian rhythm existed, and that the ratio of UH2/Ura in plasma was correlated with DPD levels in the liver of CRC rats . Furthermore, by plotting the CL tot and AUC 0‐∞ after single or repeated 5‐FU administration to CRC rats against the ratio of UH2/Ura in plasma, measured before the PK experiments, a linear relationship was inferred .…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Of note, Cyc significantly correlated with pretherapeutic leucocyte counts: Lower leucocyte counts had greater effects on the magnitude of plasma 5-FU level elevation in the second cycle. Higher 5-FU concentrations in the plasma after repeated treatment with 5-FU in animals and patients have been reported (4,5,13,14). This 5-FU elevation is related to a decrease in clearance and hepatic dihydropyrimidine dehydrogenase (DPD) activity levels (13,14).…”
Section: Final Model Bootstrap (N=1000) ----------------------------mentioning
confidence: 97%